Analisis Finansial Pekerjaan Finishing Dinding : Perbandingan Biaya Cat Konvensional Vs Pemasangan Wallpaper (Studi Kasus: Kota Palopo) - Atikah Aulia Anton; Anggel Erpa Erong Pakiding (CV. SINAR HOWUHOWU, 2026)
Wall finishing work represents a vital component in both building construction and renovation, exerting a significant impact on estimated total life-cycle costs as well as overall aesthetic value (Nurhayati & Wibowo, 2021). The selection of interior finishing materials affects not only initial financial outlays but also dictates the frequency and cumulative expenses of periodic maintenance throughout a building’s operational lifespan. This study aims to analyze and compare the financial feasibility and long-term cost efficiency between the application of conventional paint and wallpaper installation on interior walls in Palopo City. The research methodology employs a descriptive quantitative approach based on Budget Plan (Rencana Anggaran Biaya / RAB) analysis, referencing the local Unit Price of Work (Harga Satuan Pekerjaan / HSP) standards in Palopo City (Dinas PUPR Kota Palopo, 2025; Ministry of PUPR, 2022). This evaluation is enhanced through Direct Life-Cycle Costing (DLCC) modeling to assess the durability and effective service life of materials over a 10-year observation horizon (Kirk & Dell'Isola, 2015). Technical parameters regarding material degradation rates and maintenance intervals were compiled from supporting literature and local climatic conditions of Palopo City. The calculated results indicate that the initial investment cost (initial cost) for conventional paint work is IDR 28,500/m², whereas wallpaper installation requires an initial cost of IDR 68,000/m². Although conventional paint demonstrates a lower initial cost—approximately 2.38 times cheaper than wallpaper—the 10-year life-cycle cost analysis reveals a contrasting financial perspective. Due to the susceptibility of conventional paint to high humidity, which necessitates repainting every 3 years, the cumulative cost for maintenance and reapplication reaches IDR 114,000/m² by the end of the 10th year (Pratama & Supriyadi, 2023). In contrast, vinyl wallpaper proves to maintain an effective service life of up to 10 years without requiring periodic replacement, keeping its cumulative expenditure at IDR 68,000/m². This study concludes that from a long-term investment perspective, wallpaper is significantly more economical, offering a cost-saving potential of 40.3% (IDR 46,000/m²) compared to conventional paint for property owners in Palopo City.